Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Women & art: a history of women painters and sculptors from the renaissance to the 20th century - Fine, Elsa Honig (Allanheld & Schram/Prior, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Macmillan, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

From the center: feminist essays on women's art - Lippard, Lucy R. (E.P. Dutton, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis

Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper & Row, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

A history of women artists: [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present] - Munsterberg, Hugo (C. N. Potter : distributed by Crown Publishers, 1975)
A history of women artists : [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present]
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Women in the fine arts, from the seventh century B.C. to the twentieth century A.D - Clement, Clara Erskine (Hacker Art Books, 1974)
"WOMEN IN THE FINE ARTS FROM THE SEVENTH CENTURY B.C. TO THE TWENTIETH CENTURY" by Clara Erskine Clement is a historical account written in the early 20th century. The book surveys the contributions of women artists throughout history, spanning over two millennia and across multiple cultures. It aims to highlight women's roles and achievements in the fine arts, pointing out that many artists have been overlooked or forgotten despite their significant contributions. The opening of the book introduces the author's mission to gather information about women artists by reaching out to them directly, thus establishing a foundation of credibility and thoroughness for her work. Clement mentions that over a thousand women artists have been identified for this study, sharing intriguing fragments of history, such as those of ancient Greek and Roman women artist names and highlighting the cultural shifts that impacted their careers. It also critiques the lack of recorded contributions from women in the arts before the Renaissance, outlining the challenges they faced throughout different eras while paving the way for future generations of female artists. The opening sets the stage for a deeper exploration of women's artistic heritage in the following chapters. (This is an automatically generated summary.)
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques